Pengaruh Knowledge Management Terhadap Tingkat Adopsi Inovasi Budidaya Cabai Jawa Di Desa Gudangharjo Kabupaten Wonogiri - Fattah Hayu Savitri; Sapja Anantanyu; Emi Widiyanti (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Knowledge management is an important matter where java long pepper farmers can increase their self-capacity after processing the knowledge they have and acquire, where the knowledge possessed by farmers can determine behavior or attitudes in making decisions on adopting innovations influenced by farmer characteristics, communication intensity, and innovation characteristics. The research used the census method (61 java long pepper farmers) in Gudangharjo Village. The level of adoption of java long pepper cultivation innovations on CSR assisted farmers of PT. Sido Muncul which includes planting time, use of climbing poles, fertilizing, maintenance, pest control, and harvesting is in the low category overall. The results of the analysis of the influence of the intensity of communication and the characteristics of significant innovation on the level of innovation adoption among farmers assisted by CSR PT. Sido Muncul. The results of the analysis of the characteristics of farmers, are not significantly significant to the level of innovation adoption among farmers assisted by CSR PT. Sido Muncul. The R2 value is 0.533, indicating that 53.3% of the adoption rate of java long pepper cultivation innovations among farmers assisted by CSR PT. Sido Muncul can be explained by the characteristics of farmers, the intensity of communication, and the characteristics of innovation.